Exploiting mitochondria as targets for the development of new antifungals. Issue 2 (17th February 2017) - Li, Dongmei; Calderone, Richard
ABSTRACT: Mitochondria are essential for cell growth and survival of most fungal pathogens. Energy (ATP) produced during oxidation/reduction reactions of the electron transport chain (ETC) Complexes I, III and IV (CI, CIII, CIV) fuel cell synthesis. The mitochondria of fungal pathogens are understudied even though more recent published data suggest critical functional assignments to fungal-specific proteins. Proteins of mammalian mitochondria are grouped into 16 functional categories. In this review, we focus upon 11 proteins from 5 of these categories in fungal pathogens, OXPHOS, protein import, stress response, carbon source metabolism, and fission/fusion morphology. As these proteins also are fungal-specific, we hypothesize that they may be exploited as targets in antifungal drug discovery. We also discuss published transcriptional profiling data of mitochondrial CI subunit protein mutants, in which we advance a novel concept those CI subunit proteins have both shared as well as specific responsibilities for providing ATP to cell processes.